Evolution of the Microstructure and Performance of Pd/Ag - Based Thick Conductors - Maria Prudenziati; Bruno Morten; Maria Franca Brigatti (Active and Passive Electronic Components)
Pd/Ag-based inks are probably the most commonly used conductors in thick-film hybrid technology. The evolution of the microstructure of these films was studied on samples fired with isochronal cycles at a peak temperature in the range from 300℃ up to 850℃. The samples were investigated by means of X-ray diffraction, SEM and EDAX analysis techniques; the results of these analyses as well as those of thermogravimetry (TG, DTG) and differential thermal analysis (DTA), enable one to obtain a clear picture of the complex evolution of the microstructure of these conductors, which correlates quite strictly with the performance of the films in terms of resistivity and adhesion.